It’s should 5x^2+7x+3 in standard form
Answer:
A= 3
Step-by-step explanation:
4a - 7 = 5
move the constant to the right
4a= 5+7
divide
4a=12
Awnser:
A= 3
Step-by-step explanation:
(2x³y^-4)^-2 = 1/(4x⁶y^‐8) = y⁸/(4x⁶)
1/(8x⁵y^-7) = y⁷/(8x⁵)
4x^-9y⁴ = 4y⁴/x⁹
so, the whole expression is then
y⁸/(4x⁶) × y⁷/(8x⁵) × 4y⁴/x⁹
4y¹⁹/(32x²⁰) = y¹⁹/(8x²⁰)
so, D is the correct answer.
Answer:
E. √180
Step-by-step explanation:
Using Pythagoras' theorem
a^2 + b^2 = c^2 (c = hypotenuse, a and b are legs)
a^2 = c^2 - b^2
a^2 = 18^2 - 12^2
a^2 = 324 - 144
a^2 = 180
a = √180
Answer
E. √180